(untitled) (TEST Ticontre. Theory Text Translation, 2017)
Identity has been a key issue of discussion in many studies in the social sciences. Yet, approaches to this concept in Translation Studies have been largely superficial and most lack a theoretical framework. Our approach, which is based on widely recognized psychosocial theories, is intended to provide a theoretical contribution to the question of identity from a translation perspective and, more specifically, as regards the intersection of self-translation and autofiction. If identity is a discursive practice in constant reinterpretation, then (self-)translation represents a significant tool for its (de)construction. The introductive theoretical approach will be applied to the self-translated, autofictional work of Miren Agur Meabe, a living Byscayan poet; the analysis of how is (re)interpreted through self-translation may serve as a point of departure for further empirical and descriptive studies. La nozione di identità è stata un concetto chiave in molta ricerca nell’ambito delle scienze sociali. Nei Translation studies, invece, l’uso di questo concetto è spesso di carattere superficiale, poiché manca un chiaro quadro teorico. Il presente articolo intende per l’appunto fornire un contributo teorico sulla questione dell’identità dal punto di vista delle sue connessioni con la traduzione: in particolare, per quanto riguarda il ruolo dell’identità nell’autotraduzione e nell’autofiction. Se l’identità è una pratica discorsiva in constante reinterpretazione, allora l’atto di autotradursi può essere visto come un utile strumento per la sua (de)costruzione. Il quadro teorico che viene proposto nella prima parte dell’articolo, viene quindi applicato all’opera autofinzionale e autotradotto di Miren Agur Meabe, poetessa contemporanea basca. Tale analisi vuole fornire un punto di partenza per futuri studi di carattere empirico e descrittivo. PAROLE CHIAVE Self-translation; Identity; Autofiction; Social Categorization; Social Representation; Basque literature; Miren Agur Meabe.